Penerapan Model Pembelajaran Berdiferensiasi dalam Meningkatkan Minat Belajar Pendidikan Agama Islam Siswa Kelas III SDN 012 Bontang Selatan - Jannah, Raudattul; Husain, Ahmadi (NABAWI: Jurnal Penelitian Pendidikan Islam, 2025)
Abstrak - discusses the Application of Differentiated Learning Models in Increasing Interest in Learning Islamic Religious Education for Class III Students at SDN 012 South Bontang. The research aims to describe (1) the application of this research. This research aims to analyze the application of the differentiated learning model in increasing interest in learning Islamic Religious Education (PAI) of class III students at SDN 012 South Bontang. (2) The background of this research is the low interest in learning PAI among students which is often caused by teaching approaches that are less varied and do not accommodate the various needs and learning styles of students. (3) The differentiated learning model, which focuses on adapting learning materials, processes and products according to students' readiness, interests and learning profiles, is believed to be an effective solution. (4) The research method used is classroom action research (PTK) with two cycles. The research subjects were all class III students at SDN 012 South Bontang. (5) Data was collected through observation of teacher and student activities, student learning interest questionnaires, as well as documentation in the form of field notes and photographs. (6) Data analysis was carried out descriptively quantitatively and qualitatively to identify increased student interest in learning after implementing the differentiated learning model. (7) The results of the research show that the application of the differentiated learning model significantly increases interest in learning PAI for class III students at SDN 012 Bontang Selatan. (8) This improvement can be seen from students' active participation in learning activities, high enthusiasm in completing PAI assignments, and better understanding of the material. (9) Teachers also find it easy to accommodate the heterogeneous learning needs of students. (10) Thus, it can be concluded that the differentiated learning model is effective in increasing students' interest in learning PAI, so it is recommended to be applied continuously in PAI learning in elementary schools.